RETRACTED: Postoperative Pulmonary Complications in Patients With Transcatheter Tricuspid Valve Implantation—Implications for Physiotherapists - Yu, Peng-Ming; Wang, Yu-Qiang; Luo, Ze-Ruxing; Tsang, Raymond C. C.; Tronstad, Oystein; Shi, Jun; Guo, Ying-Qiang; Jones, Alice Y. M. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To investigate the incidence of postoperative pulmonary complications (PPCs) and short-term recovery after transcatheter tricuspid valve implantation (TTVI). Methods: 17 patients diagnosed with severe tricuspid regurgitation and received LuX-valve TTVI were included in this study. Spirometry-lung-function, maximal inspiratory pressure (MIP), and 6-minute walk test distance (6MWD) were recorded. Prior to surgery, patients were stratified into high or low pulmonary risk groups based on published predefined criteria. A physiotherapist provided all patients with education on thoracic expansion exercises, effective cough and an inspiratory muscle training protocol at 50% of MIP for 3 days pre-operatively. All patients received standard post-operative physiotherapy intervention including positioning, thoracic-expansion exercises, secretion-removal techniques and mobilization. Patients were assessed for PPCs as defined by the Melbourne-Group-Score-version 2. Clinical characteristics and hospital stay, cost, functional capacity, and Kansas City Cardiomyopathy Questionnaire (KCCQ) heart failure score were recorded at admission, 1-week, and 30-day post-op. Results: The mean (SD) age of the 17 patients was 68.4 (8.0) years and 15 (88%) were female. Pre-surgical assessment identified 8 patients (47%) at high risk of PPCs. A total of 9 patients (53%) developed PPCs between the 1st and 3rd day post-surgery, and 7 of these 9 patients were amongst the 8 predicted as “high risk” prior to surgery. One patient died before the 30-day follow up. Pre-operative pulmonary risk assessment score, diabetes mellitus, a low baseline MIP and 6MWD was associated with a high incidence of PPCs. Compared to those without PPCs, patients with PPCs had longer ICU and hospital stay, and higher hospitalization cost. At 30 days, patients without PPCs maintained higher MIP and 6MWD compared to those with PPCs, but there were no significant between group differences in other lung function parameters nor KCCQ. Conclusions: This is the first study to report the incidence of PPCs post TTVI. Despite a 3-day prehabilitation protocol and standard post-operative physiotherapy, PPCs were common among patients after TTVI and significantly impacted on hospital and short-term recovery and outcomes. In the majority of patients, PPCs could be accurately predicted before surgery. A comprehensive prehabilitation program should be considered for patients prior to TTVI.